Protection and (in)security beyond state: Insights from Eastern Africa and Sahel - Kasper Hoffmann; Louise Wiuff Moe; Eric Hahonou; Lotte Pelckmans (Danish Institute for International Studies (DIIS), 2015)
This report is produced under the aegis of the Defence and Security Studies research area at DIIS and contributes to the Danish and international debate about fragile and conflict-affected states. It examines key security dynamics and challenges in four conflict-affected states in Sub-Saharan Africa: the Democratic Republic of the Congo, Somaliland, Niger and Mali. It provides contextual analysis of local security dynamics with particular attention to the significance and role of local non-state actors in security provision as well as in conflict dynamics. The report analyses decisive factors behind the emergence of local security arrangements and offers insights into the interconnections between security provision, and multi-scalar conflict. The report provides knowledge of the roles played by non-state actors in dynamics of security and insecurity; it demonstrates the interconnections between politics, power struggles, and security provision, and argues that in order to support the security of these countries there is a need to address the underlying social, political and economic causes of the conflicts. To achieve that there is a need to move beyond standardised blueprints for statebuilding and security sector reform.
Keywords: 300